The Proteasome and Oxidative Stress in Alzheimer's Disease - Bonet-Costa, Vicent (Antioxid Redox Signal, 2016)
Significance: Alzheimer's disease is a neurodegenerative disorder that is projected to exceed more than 100 million cases worldwide by 2050. Aging is considered the primary risk factor for some 90% of Alzheimer's cases but a significant 10% of patients suffer from aggressive, early-onset forms of the disease. There is currently no effective Alzheimer's treatment and this, coupled with a growing aging population, highlights the necessity to understand the mechanism(s) of disease initiation and propagation. A major hallmark of Alzheimer's disease pathology is the accumulation of amyloid-β (Aβ) aggregates (an early marker of Alzheimer's disease), and neurofibrillary tangles, comprising the hyper-phosphorylated microtubule-associated protein Tau. Recent Advances: Protein oxidation is frequently invoked as a potential factor in the progression of Alzheimer's disease; however, whether it is a cause or a consequence of the pathology is still being debated. The Proteasome complex is a major regulator of intracellular protein quality control and an essential proteolytic enzyme for the processing of both Aβ and Tau. Recent studies have indicated that both protein oxidation and excessive phosphorylation may limit Proteasomal processing of Aβ and Tau in Alzheimer's disease. Critical Issues: Thus, the Proteasome may be a key factor in understanding the development of Alzheimer's disease pathology; however, its significance is still very much under investigation. Future Directions: Discovering how the proteasome is affected, regulated, or dysregulated in Alzheimer's disease could be a valuable tool in the efforts to understand and, ultimately, eradicate the disease. Antioxid. Redox Signal. 25, 886–901.